The Wounds That Do Not Heal: The Lifetime Scar of Youth Unemployment. (4th August 2021) - De Fraja, Gianni; Lemos, Sara; Rockey, James
Abstract : This paper uses UK administrative data to study the long‐term effects of unemployment on earnings. It is the first paper to pinpoint accurately the relative importance of the timing of employment shocks within workers' lives. We find a strong effect of events in the first few years after entry into the labour market: each month of unemployment between ages 18 and 20 causes a permanent income loss of 1.2% per year. This scar effect of youth unemployment is lower when it happens when the worker's age is between 21 and 23, and it disappears altogether in the next three‐year age period. The scar effect is most severe for individuals at the lower end of the ability distribution.